COHESION AND COHERENCE IN ADVERTISING DISCOURSE IN THE JAKARTA POST OF OCTOBER - DECEMBER 2018 - SESRIYANI, LODYA (Faculty of training and education, Pamulang university, 2018)
This study is aimed at finding out the cohesion and coherence in advertising discourse in The Jakarta Post as well as its implication of the study in teaching reading and writing. The writer used purposive sampling as the method of collecting data. The writer took the data from editions of The Jakarta Post published in October- December 2018. The writer used a cohesion theory suggested by Halliday and Hasan (1976) in analyzing the data. On the contrary in coherence analysis the writer generated Peirce?s semiotic theory of sign (2007) and speech act theory proposed by Austin (1962). Thus, in analyzing the aspect of coherence the writer focused on recognizing and identifying the function of headline as well as the pictures with respect to illocutionary meaning and semiotic meaning. The results of such analysis show that there are three cohesive devices frequently used in the advertising discourse. They are lexical cohesion (51.61%), then reference (25.81%), then substitution (20.97%), and followed by conjunction (4.84%) in which the most presupposed item tends to refer to what is advertised. On the other hand, the headlines and images are both coherent with the idea of the written discourse and speech act meaning as suggested by Austin?s theory. The pictures in the advertising discourse have implication on cultural, social and mythical ideology as suggested by Peirce?s theory of sign. Based on the findings of this research, it can be concluded that the understanding of cohesion and coherence for students will greatly affect the ability of students in reading, interpreting and writing a text. In order to improve the students? proficiency, it is important to introduce variety of texts such as advertising discourse for students especially in University.